Language switching and domain-general control in interpreters - Nour, Soudabeh; Struys, Esli (Frontiers in Language Sciences, 2023)
The purpose of this paper is to examine whether and how the training and professional experience in interpreting affect task switching in this bilingual population. In the first experiment, we compared a group of interpreting students to translation students using the Bilingual categorization task to test their language-switching (domain-specific) at pre-and post-training. In the second experiment, we added a group of professional interpreters to the participants in experiment 1, to test prepotent response inhibition using the Simon task (domain-general). First, the results showed training-related improvement in the bilingual categorization task in both student groups, indicating a similar effect for translation and interpreting training. Second, both student groups showed better performance on the Simon task compared to professional interpreters, but only on response times and not on accuracy. The correlation analyses of the two tasks in student groups only showed significant correlations between the global RTs, and between the forward-switch costs of both tasks specifically for the translation students, indicating domain-generality between language and cognitive control only to a limited extent. Considering language background, the onset age of L2 acquisition (AOA2) in the interpreting students was significantly correlated with the congruency effect in the Simon task, indicating an impact of language background on domain-general control. Results were discussed in the light of the different engaging elements including task specificity, research method, participants’ language profile, and the replication factor.